The Role of Temporal Acoustic Exaggeration in High Variability Phonetic Training: A Behavioral and ERP Study - Cheng, Bing; Zhang, Xiaojuan; Fan, Siying; Zhang, Yang (Frontiers in Psychology, 2019)
High variability phonetic training (HVPT) has been found to be effective in helping adult learners acquire nonnative phonetic contrasts. The present study investigated the role of temporal acoustic exaggeration by comparing the canonical HVPT paradigm without involving acoustic exaggeration with a modified adaptive HVPT paradigm that integrated key temporal exaggerations in infant-directed speech (IDS). Sixty native Chinese adults participated in the training of the English /i/ and /ɪ/ vowel contrast and were randomly assigned to three subject groups. Twenty were trained with the typical HVPT (the HVPT group), twenty were trained under the modified adaptive approach with acoustic exaggeration (the HVPT-E group), and twenty were in the control group. Behavioral tasks for the pre- and post- tests used natural word identification, synthetic stimuli identification, and synthetic stimuli discrimination. Mismatch negativity (MMN) responses from the HVPT-E group were also obtained to assess the training effects in within- and across-category discrimination without requiring focused attention. Like previous studies, significant generalization effects to new talkers were found in both the HVPT group and the HVPT-E group. The HVPT-E group, by contrast, showed greater improvement as reflected in larger progress in natural word identification performance. Furthermore, the HVPT-E group exhibited more native-like categorical perception based on spectral cues after training, together with corresponding training-induced changes in the MMN responses to within- and across- category differences. These data provide the initial evidence supporting the important role of temporal acoustic exaggeration with adaptive training in facilitating phonetic learning and promoting brain plasticity at the perceptual and pre-attentive neural levels.